المسائل التي على خلاف القياس عند متأخري الحنابلة في كتاب الطهارة جمعاً ودراسة: Late Hanbali Scholars' Views on Issues That Contradict Analogy in the Book of Purification - Saleh bin Mohammed bin Saleh Al-Dakhil (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The objective of this research is to examine issues related to analogy (qiyas) that the Hanbalis disagreed with in the Book of Purification, to explain the origins of the qiyas in these disputed matters, and to analyze why the Hanbalis diverged from qiyas. It also explores the views of non-Hanbalis on these issues and aims to determine the strongest opinion among them. The study adopts an inductive approach by exploring sources relevant to the topic and a deductive comparative approach by presenting the views of jurists, their arguments, and responses, followed by determining the strongest opinion and its supporting evidence. The research concludes that the Hanbali school sometimes departs from its principles and rules due to other factors, such as textual evidence from the Prophet (PBUH) or reports from some companions.